FORMULATION AND EVALUATION OF HERBAL UNDER EYE CREAM CONTAINING NELUMBO NUCIFERA AND RUBIA CARDIFOLIA - Barguje Dhanshri Santosh; Shinde Tejas Nandkumar; Shinde Parth Rajendra; Pachpute Sanket Mohan; Kulange Sanket Sunil; Garud Neha Sunil; *, Pawar Pratiksha Babusha; Dr. Khedkar Amol Navnath; Sake Vaishnavi Sanjay; Lagad Rutuja Devidas (The Bioscan, 2026)
The current study focuses on creating and assessing a herbal under-eye cream with extracts from Nelumbo nucifera (lotus seed) and Rubia cordifolia (manjistha) for antioxidant and anti- pigmentation properties. Stress, pigmentation, poor blood circulation, and oxidative damage are the main causes of dark circles, a frequent cosmetic issue. The antioxidant, skin-soothing, and melanin-reducing qualities of the herbal extracts led to their selection. Stearic acid, beeswax, coconut oil, glycerin, triethanolamine, rose water, methyl and propyl paraben, and other excipients were used in the emulsification process to make the cream. Herbal extracts were prepared in different formulation batches with different concentrations. A number of characteristics, including appearance, pH, homogeneity, spreadability, washability, viscosity, and stability, were assessed for the prepared creams. The formulated herbal under-eye cream demonstrated excellent consistency and physical properties ideal for topical application. By combining Manjistha and lotus seed extract, the cream provides a powerful synergistic effect that safely reduces dark circles and protects the delicate under-eye skin from oxidative damage. Manjistha targets inflammation and hyperpigmentation through active compounds like purpurin, flavonoids, and phenols that fight free radicals. Concurrently, lotus seed extract calms the skin and blocks excess melanin production. Ultimately, the study confirms that this natural cosmetic blend offers a highly effective, safe, and antioxidant-rich solution for treating dark circles and preventing skin damage